ANALYSIS OF PATIENT IDENTIFICATION COMPLIANCE BY NURSE IN GENERAL WARD OF ISLAMIC HOSPITAL MALANG - Zamanti, Arfiyani; Wardani, Diadjeng Setya; Duhitatrissari, Fifin Pradina (Journal of Community Health and Preventive Medicine, 2025)
Patient safety is a system created by hospital to ensure safer healthcare. One of the aspects of patient safety is patient identification. Patient misidentification at the beginning of the service will lead to further errors in later processes. Misidentification will cause harm to patients and bring lawsuit against the hospital. The study aimed to identify factors influencing compliance with patient identification and explore 2 aspects of patient identification, ID wristband check and the use of at least 2 patient’s identifiers. The quantitative descriptive study was conducted in Unisma Islamic Hospital Malang using questionnaires and observations to collect data. Respondents for the questionnaires were 40 nurses of 4 inpatient wards, Jasmine, Tulip, Teratai, and Dahlia. There were 20 participants of the observations. The result of the questionnaires shows that the score of attitude was 94.4% (good), the sore of team work was 63.3% (quite good), the score of work environment reached 95.6% (supporive),and the score of knowledge was 81,6% (good). However, the result of the observations reveals that compliance with patient identification was 81%, which is 19 % below the standard 100%. This is caused by lack of nurses’ understanding regarding accurate patient identification procedure, insufficient supervision, and weak patient safety culture. To improve patient identification compliance, active participation of the management, the patients and their family is required.